Correction: Capturing sexual contact patterns in modelling the spread of sexually transmitted infections: Evidence using Natsal-3. - Samik Datta; Catherine H Mercer; Matt J Keeling (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0206501.].